2021
DOI: 10.1089/acm.2020.0383
|View full text |Cite
|
Sign up to set email alerts
|

Garnering Support for Complementary and Integrative Health Implementation: A Qualitative Study of VA Healthcare Organization Leaders

Abstract: Objectives: Healthcare organization leaders' support is critical for successful implementation of new practices, including complementary and integrative health (CIH) therapies. Yet little is known about how to garner this support and what motivates leaders to support these therapies. We examined reasons leaders provided or withheld support for CIH therapy implementation, using a multilevel lens to understand motivations influenced by individual, interpersonal, organizational, and system determinants.Design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Prior research in VA demonstrated the positive impact of CIH therapies such as yoga, Tai Chi, acupuncture, and mindfulness practices for Veterans, [13][14][15][16][17][18] yet the implementation of these services had up to that point been unsystematic and poorly coordinated overall. [19][20][21] In response, OPCC&CT formalized the WHS, and in October 2017, each Veterans Integrated Service Network (VISN -regional networks) identified and funded a WH flagship VA medical center for a 3-year WHS pilot. The evaluation was to culminate in April 2020 in a congressional report, including key findings on the pilot's impact on Veterans.…”
Section: Policy "Window Of Opportunity"mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research in VA demonstrated the positive impact of CIH therapies such as yoga, Tai Chi, acupuncture, and mindfulness practices for Veterans, [13][14][15][16][17][18] yet the implementation of these services had up to that point been unsystematic and poorly coordinated overall. [19][20][21] In response, OPCC&CT formalized the WHS, and in October 2017, each Veterans Integrated Service Network (VISN -regional networks) identified and funded a WH flagship VA medical center for a 3-year WHS pilot. The evaluation was to culminate in April 2020 in a congressional report, including key findings on the pilot's impact on Veterans.…”
Section: Policy "Window Of Opportunity"mentioning
confidence: 99%
“…Moreover, it required an evaluation of the effect of CIH and other approaches on the health and well‐being of Veterans. Prior research in VA demonstrated the positive impact of CIH therapies such as yoga, Tai Chi, acupuncture, and mindfulness practices for Veterans, 13–18 yet the implementation of these services had up to that point been unsystematic and poorly coordinated overall 19–21 . In response, OPCC&CT formalized the WHS, and in October 2017, each Veterans Integrated Service Network (VISN ‐ regional networks) identified and funded a WH flagship VA medical center for a 3‐year WHS pilot.…”
Section: Introductionmentioning
confidence: 99%
“…Clinic leadership may have varied opinions on whether CIH interventions are effective, which may or may not be a barrier toward implementation. 46 Moreover, clinicians often must weigh available clinic resources with patient symptom severity and patient choice. By highlighting that patients will use these therapies if they are offered, the present data may encourage other healthcare settings and clinics to continue to expand their availability as these data demonstrate “If it is built, they will come.” In turn, engagement in these treatments can potentially improve targeted outcomes.…”
Section: Discussionmentioning
confidence: 99%